An Overview of Ecotherapy-Based Activities in Urban Green Spaces Design - Aristyowati Aristyowati; Evawani Ellisa (AIBPM Publisher, 2021)
This research aims to see an overview of ecotherapy-based activities as a form of intervention in the design of urban green spaces during the pandemic. Ecotherapy is a combined approach of socio-ecological strategy that promotes mental health, through community participation and empowerment. The ecotherapy-based activities include horticultural therapy such as gardening and physical therapy such as sports activities. The research method is a qualitative method through case studies. The case study was carried out at two locations of Taman Maju Bersama which in 2020 had conducted a Focus Group Discussion (FGD) process at the planning stage. The impact of the COVID-19 virus outbreak presents an opportunity to integrate a public health perspective into the concept of urban green space design standards. This is an opportunity to improve urban green space design standards that need to be considered by the Jakarta Provincial Government in the future. Some considerations should be included: 1) the opportunity to improve urban green space on a neighborhood scale, 2) the potential for an ecotherapy approach, especially on spatial program interventions in urban green spaces design, 3) consideration of health protocol policies for handling COVID-19, such as a new interpersonal physical distance limit in urban public spaces.